2011
DOI: 10.1021/jf104018u
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Radix Astragali Induce the Expression of Erythropoietin in Cultured Cells: A Signaling Mediated via the Accumulation of Hypoxia-Inducible Factor-1α

Abstract: Radix Astragali (RA) is commonly used as a health food supplement to reinforce the body vital energy. Flavonoids, including formononetin, ononin, calycosin, and calycosin-7-O-β-d-glucoside, are considered to be the major active ingredients within RA. Here, we provided different lines of evidence that the RA flavonoids stimulated the expression of erythropoietin (EPO), the central regulator of red blood cell mass, in cultured human embryonic kidney fibroblasts (HEK293T). A plasmid containing hypoxia response el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 29 publications
1
71
0
2
Order By: Relevance
“…12 This suggests that the pHRE-Luc activity of jujube does not relate to the content of flavonoids. In parallel to this notion, flavonoids derived from herbal medicines have been reported to be able to induce the expression of EPO, 29 suggesting that flavonoids may be one of the active ingredients for this action.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 96%
“…12 This suggests that the pHRE-Luc activity of jujube does not relate to the content of flavonoids. In parallel to this notion, flavonoids derived from herbal medicines have been reported to be able to induce the expression of EPO, 29 suggesting that flavonoids may be one of the active ingredients for this action.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 96%
“…For the past decades, our group has studied several decoctions with Astragalius Radix, such as Danggui Buxue Tang [16] [17] [18]; Fo Shou San and Yu Ping Feng San [19] [20] [21]. Astragalius Radix was able to abolish the ubiquity in degradation system and resulted the accumulation of hypoxia inducible factor 1 alpha (HIF-1α) [22] [23]. Thus, a pseudo-hypoxic environment could be generated at cellular level.…”
Section: Resultsmentioning
confidence: 99%
“…Radix astragalus has a comprehensive and sustained effect in elevating whole blood cells, recovering red blood cell, while blood cell, and platelet levels to normal. In addition, it promotes the secretion of hematopoietic cytokine, stimulating the function of the hematopoietic system, and counteracting bone marrow suppression caused by chemotherapy and radiotherapy (Gao et al, 2006;Zheng et al, 2011). In summary, modern medicine has demonstrated that the spleen and kidney have the dual role of promoting the regulation of hematopoietic cell proliferation and immune function.…”
Section: Discussionmentioning
confidence: 99%